Model Pengembangan Kurikulum dan Pembelajaran Pendidikan Agama Islam di Era Modern - Mitra Samita; Ifah Khadijah; Usep Suherman; Rahma Dilla Zainuri; Haerudin Haerudin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
Research on Islamic Religious Education (PAI) curriculum and learning is a strategic instrument in encouraging innovation in Islamic education amidst the dynamics of scientific and technological developments and social change. This article aims to analyze the concept of developing PAI curriculum and learning research, identify key issues faced in educational practice, and formulate a relevant and applicable research development model. The study results indicate that the development of PAI curriculum and learning research needs to be directed at integrating revealed values with modern pedagogical approaches in a systematic and sustainable manner. This concept positions Islamic Religious Education (PAI) not only as a means of transferring religious knowledge, but also as a process of character formation, strengthening faith, and fostering social responsibility in students. The main problems faced in developing Islamic Religious Education (PAI) curriculum and teaching include low innovation in learning methods, limited competency and resources of educators and researchers, a lack of relevance of the material to technological developments and social contexts, and a lack of research based on the real needs of students. Therefore, this article recommends a model for developing Islamic Religious Education curriculum and learning research that combines Research and Development (R&D), Design-Based Research (DBR), and Action Research approaches with Islamic educational principles. Implementation of this model is carried out through stages of trial and error, reflection, and continuous evaluation. Thus, Islamic Religious Education curriculum and learning research is expected to improve learning effectiveness, encourage educational innovation, and realize the goals of Islamic education in developing knowledgeable, faithful, and morally upright individuals.